2016
DOI: 10.1016/j.jad.2016.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime heart rate predicts response to depression treatment in patients with coronary heart disease

Abstract: Background Previous studies suggest that patients with coronary heart disease (CHD) who do not respond to treatment for depression are at higher risk of mortality than are treatment responders. The purpose of this study was to determine whether elevated nighttime heart rate (HR) and low heart rate variability (HRV), both of which have been associated with depression and with cardiac events in patients with CHD, predict poor response to depression treatment in patients with CHD. Methods Patients with stable C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…We found an association between greater heart rate variability and a favourable depression outcome, which is in line with previous findings where heart rate variability is discussed as a marker of emotional dysregulation and predicts an increased disease risk [5355]. One study could show that a low (nighttime) heart rate variability was a significant predictor of a poor response to treatment of major depression in patients with stable CAD [56]. Caldwell et al (2018) suggest the use of a heart rate variability biofeedback in combination with psychotherapy, improving the outcome of depression treatment [53].…”
Section: Discussionsupporting
confidence: 91%
“…We found an association between greater heart rate variability and a favourable depression outcome, which is in line with previous findings where heart rate variability is discussed as a marker of emotional dysregulation and predicts an increased disease risk [5355]. One study could show that a low (nighttime) heart rate variability was a significant predictor of a poor response to treatment of major depression in patients with stable CAD [56]. Caldwell et al (2018) suggest the use of a heart rate variability biofeedback in combination with psychotherapy, improving the outcome of depression treatment [53].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, by using nonlinear techniques to automatically classify the HRV signals of healthy people and those at risk of sudden cardiac death (SCD), Fujita [ 61 ] demonstrated that HRV was able to identify the person at four minutes prior to SCD. Carney [ 62 ] recently showed that high heart rate and low HRV during nighttime could be used as a predictor of the poor response to the treatment of major depression and of the higher risk for mortality in patients with stable coronary heart disease. This study further clarifies the association between sleep HRV and CVD, and establishes the role of hypnopompic HRV in the automatic prediction of short-term CVD events.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for not detecting possible effects could be that our methods for assessing depressive symptoms or heart rate variability were not valid enough and therefore could not detect existing differences. Other studies have used clinical diagnostic interviews to assess depression [38,39]; however, for example Francis et al used questionnaires to assess depression and could identify the postulated associations [40]. The PHQ-9, which we used in our study, has the advantage that it can simultaneously be used as a diagnostic algorithm to make a probable diagnosis of major depressive disorder or as a continuous measure of depressive symptoms and is equal or superior to similar instruments [41].…”
Section: Patients Characteristicsmentioning
confidence: 97%